ORGANISM, ENVIRONMENT, LITERATURE: MARY SHELLEY’S INVESTIGATION OF NATURAL & SEXUAL SELECTION IN FRANKENSTEIN - Jagt, Tyler H (Wake Forest University, 2019)
This thesis examines Mary Shelley’s debut novel Frankenstein in tandem with the evolutionary theory presented across Erasmus Darwin’s poetry and scientific publications. The Botanic Garden, The Temple of Nature, and Zoonomia are not typically considered when inquiring of Shelley, and evolutionary theory has been neglected as an effective lens for potential interpretations of Frankenstein. This project seeks to highlight how the earlier Darwin’s texts are perhaps taken up and considered by Shelley, and foregrounds their potential influence on the creation of her novel. Darwin’s poetry acted as a vehicle for transporting evolutionary understanding to the public mind, and his theories in Zoonomia specifically highlight how male specimen evolve through a type of natural selection when competing for the females in their environment. Here, Erasmus shows an early understanding of how sexual selection may work, although it lacks complete empirical footing. Among the various scientists her work may consider, Shelley appraises and deliberates Erasmus’ theories in particular, creating a narrative that imagines an evolutionary step backwards, from dual-sex to single-sex reproduction at the exclusion of the female sex. This thesis therefore considers the gender politics of both Darwin and Shelley’s writing, and frames itself through a feminist lens as it explores Shelley’s response to Erasmus, and her reinterpretation of Romantic evolutionary thought.
Keywords: Erasmus Darwin; Evolution; Frankenstein; Mary Shelley; Romanticism; Science